Production of Trichophyton mentagrophytes antigens and their characterization in mice - Venturini, J. [UNESP]; Rossi-Ferreira, R. [UNESP]; Arruda, M. S. P. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
The participation of dermatophytic antigens in the host-parasite balance is still poorly understood. One of the difficulties encountered by researchers is the lack of dominant and specific antigens that can be used in such studies. In order to contribute to a better understanding of this aspect of infection, the present study identifies antigen fractions obtained from exoantigen and cytoplasmic extracts of Trichophyton mentagrophytes. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) revealed the presence of 13 proteins in the exoantigen extract, whose molecular weight ranged from 12.5 to 90 kDa. The cytoplasmic extract contained 18 protein fractions ranging from 11 to 110 kDa. Immunoblotting showed the presence of immunodominant antigens against IgG, IgM and IgA antibodies. This affinity was observed in three proteins of the exoantigen extract and in three proteins of the cytoplasmic extract, with respective molecular weights of 33, 39 and 59, and 40, 55 and 82 kDa. These results are promising, especially when considering that these extracts contain antigenically distinct protein fractions which, once determined, may contribute to a better understanding of dermatophytoses, and may thus help in the development of alternative strategies for the diagnosis and treatment of this condition.
Keywords: Trichophyton mentagrophytes; antigens